Mechanical properties and cutting performance of TiCN-based cermets fabricated by spark plasma sintering. (2018) - Tang, Siwen; Liu, Deshun; Li, Pengnan; Jiang, Lingli; Niu, Qiulin
TiCN-based cermet cutting tools were fabricated by spark plasma sintering. The effect of each component on mechanical properties and cutting performance was studied. The results show that the density, strength, and hardness of TiCN-based cermets can be improved by adding SiCw and La2 O3 . Compare to TiCN-5Co cermets, TiCN-5Co-1SiCw and TiCN-5Co-1SiCw -1La2 O3 obtained good mechanical properties. Cutting experiments showed that the cutting force on a TiCN-5Co-1SiCw -1La2 O3 tool was significantly reduced compared to that on a TiCN-5Co-1SiCw tool; meanwhile, the wear resistance of TiCN-5Co-1SiCw -1La2 O3 was enhanced to a significant extent.